Self-Management Skills Of School Administrators In Relation To Teachers’ Productivity In Public Elementary Schools - Aurelio Jr, S. Gomez; Suhendra Suhendra (Universitas Pakuan, 2025)
This study was conducted to determine the relationship between the self-management skills of school administrators in relation to teachers' productivity of public elementary schools of District of Sta. Cruz South, Division of Davao del Sur, Digos City. The study used the non- experimental quantitative research design utilizing correlational method. The respondents were composed of 201 teachers in the public secondary schools using a simple random sampling. The statistical tools used were Mean, Pearson Product Moment Coefficient Correlation (Pearson r) and Regression Analysis. The level of self-management skills was oftentimes manifested by the school administrators. Meanwhile, the level of teachers' productivity of public elementary schools is oftentimes practiced by the teachers. There was a significant relationship between the self-management skills of school administrators in relation to teachers' productivity of public elementary schools. The domains of self-management skills of school administrators were significantly influenced the teachers' productivity of public elementary schools. It was also disclosed that the school administrators should assess their self-management skills in terms of stress management, time management, organizing skills, problem solving, decision making skill, and confidence so that they can make necessary refinement for improvement of the cited skills. It is mentioned in this study that self-management skills of school administrators and teachers' productivity of public elementary schools should be raised in a very high level. Therefore, this study suggests that the self-management skills of school administrators should be augmented to a very high level to facilitate the teachers' productivity of public elementary schools.